Research on The Negative Role of Internet Memes in Youth Communication and The Correct Guidance Strategy - Zhang Qing (Ilmu Inovasi Nusantara, 2025)
In the era of rapid Internet development, Internet memes have become highly popular among young people due to their unique expression and widespread dissemination. Memes reflect their emotions and state of mind and serve as a means for observing social phenomena and cultural trends. The popularity of Internet memes provides young people with new forms of communication and expression in complex social environments while fostering creative thinking and observation. However, due to their varied meanings and potential misuse, Internet memes can influence and shape young people's values and worldviews, sometimes leading to adverse effects. This study aims to analyze the impact of Internet memes on developing young people's values and explore appropriate ways to integrate memes into ideological and political education. A qualitative research approach is employed, utilizing literature analysis and case studies to understand how young people use and perceive memes. The findings indicate that while memes can serve as creative tools for social reflection, their uncontrolled use can lead to misinformation, oversimplification of complex issues, and the formation of uncritical thinking patterns. Therefore, a deeper understanding of appropriate meme usage and the role of educators in guiding young people is essential. Digital literacy-based educational approaches should be implemented to help young people understand memes' meaning, context, and social impact. Additionally, thoughtful supervision and regulations that do not stifle creativity should be applied to ensure the healthy and positive development of Internet memes